No signs of check-list fatigue – introducing the StOP? intra-operative briefing enhances the quality of an established pre-operative briefing in a pre-post intervention study - Timm-Holzer, Eliane; Tschan, Franziska; Keller, Sandra; Semmer, Norbert K.; Zimmermann, Jasmin; Huber, Simon A.; Hübner, Martin; Candinas, Daniel; Demartines, Nicolas; Weber, Markus; Beldi, Guido (Frontiers in Psychology, 2023)
Background The team timeout (TTO) is a safety checklist to be performed by the surgical team prior to incision. Exchange of critical information is, however, important not only before but also during an operation and members of surgical teams frequently feel insufficiently informed by the operating surgeon about the ongoing procedure. To improve the exchange of critical information during surgery, the StOP?-protocol was developed: At appropriate moments during the procedure, the leading surgeon briefly interrupts the operation and informs the team about the current Status (St) and next steps/objectives (O) of the operation, as well as possible Problems (P), and encourages questions of other team members (?). The StOP?-protocol draws attention to the team. Anticipating the occurrence of StOP?-protocols may support awareness of team processes and quality issues from the beginning and thus support other interventions such as the TTO; however, it also may signal an additional demand and contribute to a phenomenon akin to “checklist fatigue.” We investigated if, and how, the introduction of the StOP?-protocol influenced TTO quality. Methods This was a prospective intervention study employing a pre-post design. In the visceral surgical departments of two university hospitals and one urban hospital the quality of 356 timeouts (out of 371 included operation) was assessed by external observers before (154) and after (202) the introduction of the StOP?-briefing. Timeout quality was rated in terms of timeout completeness (number of checklist items mentioned) and timeout quality (engagement, pace, social atmosphere, noise). Results As compared to the baseline, after the implementation of the StOP?-protocol, observed timeouts had higher completeness ratings (F = 8.69, p = 0.003) and were rated by observers as higher in engagement (F = 13.48, p < 0.001), less rushed (F = 14.85, p < 0.001), in a better social atmosphere (F = 5.83, p < 0.016) and less noisy (F = 5.35, p < 0.022). Conclusion Aspects of TTO are affected by the anticipation of StOP?-protocols. However, rather than harming the timeout goals by inducing “checklist fatigue,” it increases completeness and quality of the team timeout.